STUDENTS’ PERCEPTION OF SNOWBALL THROWING IN TEACHING GRAMMAR - Yanuarti Apsari; Indra Andriana Saputra; Gian Leriandini (IKIP Siliwangi, 2019)
The aim of the research is to investigate students’ perception of snowball throwing technique in teaching grammar. The research used qualitative descriptive research method and the participants of the research were second grade of SMPN 2 Padalarang. The data were obtained from questionnaire and interview. Questionnaire was used to obtain information about students' perception towards the implementation of snowball throwing in teaching grammar and interview was also used to get more specific information that cannot be accessed through questionnaire. From the questionnaire, the students answered strongly agree is 66,67%, agree 19,44% and disagree 13,89% that this technique is good to be implemented in teaching grammar. Therefore, the result shows that the implementation of snowball throwing technique in teaching grammar can help students to learn English grammar. Based on questionnaire and interview, they enjoyed learning with this technique and they showed some improvement on their participation of learning activity, their their creativity and their cooperative skill when learning with this technique.Keywords: Grammar, Snowball Throwing Technique , Students’ Perception.